2011
DOI: 10.1053/j.gastro.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Duct Cells Contribute to Regeneration of Endocrine and Acinar Cells Following Pancreatic Damage in Adult Mice

Abstract: BACKGROUND & AIMS There have been conflicting results on a cell of origin in pancreatic regeneration. These discrepancies predominantly stem from lack of specific markers for the pancreatic precursors/stem cells, as well as differences in the targeted cells and severity of tissue injury in the experimental models so far proposed. We attempted to create a model that used diphtheria toxin receptor (DTR) to ablate specific cell populations, control the extent of injury, and avoid induction of the inflammatory res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
114
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(121 citation statements)
references
References 35 publications
4
114
0
Order By: Relevance
“…This observation may provide an explanation for previous publications showing that Sox9 + ductal cells and other pancreatic ductal cells did not differentiate into β cells in Alloxaninduced diabetic mice after 1 wk of treatment with GE (14); this finding also provides an explanation for the lack of Sox9 + ductalderived β cells in STZ-induced diabetic mice with high hyperglycemia (∼500 mg/dL) and in the absence of administration of growth factors (16,18). Therefore, we agree with a recent review by Lysy et al that neogenesis from ducts is influenced by the type and extent of pancreatic injury as well as dependent on the affected cell types (30,31).…”
Section: Discussionsupporting
confidence: 91%
“…This observation may provide an explanation for previous publications showing that Sox9 + ductal cells and other pancreatic ductal cells did not differentiate into β cells in Alloxaninduced diabetic mice after 1 wk of treatment with GE (14); this finding also provides an explanation for the lack of Sox9 + ductalderived β cells in STZ-induced diabetic mice with high hyperglycemia (∼500 mg/dL) and in the absence of administration of growth factors (16,18). Therefore, we agree with a recent review by Lysy et al that neogenesis from ducts is influenced by the type and extent of pancreatic injury as well as dependent on the affected cell types (30,31).…”
Section: Discussionsupporting
confidence: 91%
“…PDL has been extensively used to study the conversion of ADM into PDAC [1,3] as well as a method of duct-to-islet differentiation [6,[8][9][10][11][12] in order to increase beta-cell mass. However, contradictory results have been obtained from the conventional mouse models [6,7,11,26].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic duct ligation (PDL) in mouse models has been extensively used as a model of chronic pancreatitis in order to study the evolution of ADM into PDAC [1,3,7], and also as a model of duct-to-islet differentiation [6,[8][9][10][11][12] to increase beta-cell mass. However, the validity of PDL as a model of endocrine regeneration has now been called into question [5][6][7]11,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrastructural, inmunohistochemical and studies with transgenic mice have demonstrated that after correct experimental duct ligation, most of the acinar cells are rapidly and massively deleted by p53-dependent apoptosis by caspase activation with some pancreatic epithelial proliferation 1,2,37-40 and beta-cell neogenesis by newly formed islet-like cell clusters 21,41,42 . In our study, all these histological signs were clearly demonstrated in the distal pancreas of RF transected pancreas in comparison to proximal pancreas and the pancreas of sham and control groups with appropriate inmunohistochemical staining.…”
Section: Discussionmentioning
confidence: 99%
“…As some authors have suggested, the extent of pancreatic acinar cell apoptosis have been shown to be inversely related to the severity of pancreatic injury, suggesting that induction of a rapid and massive acinar cell apoptosis is a protective action against acute pancreatitis [42][43][44][45] . Likewise, Girelli et al, 25 interestingly observed that tumor-related obstruction of the main pancreatic duct may reduce the risk of acute pancreatitis after RF pancreatic ablation.…”
Section: Discussionmentioning
confidence: 99%